Beta-blocker administration within 24 hours after admission to the intensive care unit and mortality in critical heart failure patients: a retrospective analysis from the MIMIC-IV database - Xie, Linfeng; Chen, Jing; Li, Yuanzhu; Liu, Gang; Shen, Jian; Li, Xiang; Yang, Yuan; Chen, Yintao; Luo, Suxin; Huang, Bi (Frontiers in Pharmacology, 2025)
BackgroundIt remains poorly understood whether early use of beta-blockers could provide a survival advantage in patients with critical heart failure (HF) .MethodsThis retrospective study was conducted using the American Medical Information Mart for Intensive Care (MIMIC)-IV database. Study participants were critical HF patients who were divided into two groups: within 24-hour use of beta-blockers group and no use of beta-blockers group. The primary study endpoints were 7-day, 30-day, and 360-day all-cause mortality.ResultsOut of the 10,184 patients diagnosed with critical HF, after propensity score match (PSM), 7352 patients were recruited and were divided into within 24-h use of beta-blockers group (n = 3676) and no beta blockers group (n = 3676). The 7-day, 30-day, and 360-day all-cause mortality were significantly higher in the no beta blockers group (7-day: 10.3% vs 5.5%; 30-day: 21.4% vs 15.7%; 360-day: 40.0% vs 35.3%; all p < 0.001). Kaplan–Meier analyses showed that the cumulative incidence of 7-day, 30-day, and 360-day all-cause mortality were significantly higher in the no beta blockers group (all log-rank p < 0.001). After PSM, Cox proportional hazards analyses revealed that beta blockers administration within 24 h of admission to intensive care unit (ICU) was independently associated with decreased 7-day (HR = 0.52 95%CI: 0.44, 0.62, p < 0.001), 30-day (HR = 0.70 95%CI: 0.63, 0.78, p < 0.001), and 360-day (HR = 0.83 95%CI: 0.77, 0.89, p < 0.001) all-cause mortality.ConclusionAdministration of beta blockers within 24 h after admission to ICU was associated with reduced risk of mortality in critical HF patients. However, prospective randomized controlled trials are needed to confirm our findings due to the retrospective nature of the present study and the limitations of the MIMIC-IV database itself.